Urban and Regional Policy and its Effects - Wolman, Harold; Wial, Howard; Pindus, Nancy, $eeditor (Book collections on Project MUSE., 2014)
Urban and Regional Policy and Its Effects, the second in a series, sets out to inform policymakers, practitioners, and scholars about the effectiveness of select policy approaches, reforms, and experiments in addressing key social and economic problems facing cities, suburbs, and metropolitan areas. The chapters analyze responses to six key policy challenges that most metropolitans areas and local communities face: Creating quality neighborhoods for families; Governing effectively; Building human capital; Growing the middle class; Growing a competitive economy through industry-based strategies; Managing the spatial pattern of metropolitan growth and development. Each chapter discusses a specific policy topic under one of these challenges. The authors present the essence of what is known, as well as the likely implications, and identify the knowledge gaps that need to be filled for the successful formulation and implementation of urban and regional policy. Contributors: Karen Chapple and Rick Jacobus (University of California, Berkeley and Burlington Associates), Jeffrey R. Henig and Elisabeth Thurston Fraser (Teachers College, Columbia University), W. Norton Grubb (University of California, Berkeley), Harry J. Holzer (Georgetown University and Urban Institute), Susan Christopherson and Michael H. Belzer (Cornell University and Wayne State University), and Rolf Pendall (Cornell University).